Cost-effectiveness analysis of surgical lung volume reduction compared with endobronchial valve treatment in patients with severe emphysema (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY / PRINCIPLES: Colonoscopies are complex procedures that depend greatly on the patient’s cooperation and on the correct judgment of a tolerable amount of discomfort by the endoscopy team, even in sedated patients. Little is known regarding the accuracy of the patient comfort level assessments made by medical staff.METHODS: We prospectively evaluated the degree of agreement between the assessments made by the endoscopists and endoscopy nurses and the assessments made by patients regarding their comfort level during the procedure. A total of 222 patients scheduled for routine colonoscopies assessed their preprocedural anxiety and the tolerability of the procedure. Endoscopists and nurses assessed the difficulty of the examination and the patient’s level of discomfort. Assessments were performed using a 100-mm VAS.RESULTS: Overall, patients rated the procedure as tolerable. For 12% (27/222) of the patients, the examination was less tolerable (VAS >50 mm). The patients’ judgment of tolerability was not related to the initial level of anxiety (r = 0.15). The scores of the endoscopists and nurses were better correlated with each other (r = 0.58) than with the patients’ self-assessments (r = 0.37 and 0.35, respectively). Both endoscopists and nurses tended to overestimate the patients’ discomfort. However, in 9% (19/222) of cases, the level of patient discomfort was considerably underestimated by at least one member of the team.CONCLUSION: Our study shows that the estimation of a patient’s discomfort during a colonoscopy is difficult and that the comfort level may not be accurately determined in a considerable number of patients, including sedated patients.